2020
DOI: 10.1037/hea0001027
|View full text |Cite
|
Sign up to set email alerts
|

Role of childhood maltreatment on weight and weight-related behaviors in adulthood.

Abstract: This study investigated associations between child maltreatment and body mass, body weight perceptions, and weight control behaviors among men and women. Method: Data were derived from the National Longitudinal Study of Adolescent to Adult Health (Add Health). Multinomial logistic regression was used to investigate links between dimensions of childhood maltreatment and adult (a) classifications of body mass index (BMI), (b) discrepancies in perceived weight and actual BMI categories, and (c) normative and risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
5
14
2
Order By: Relevance
“…Importantly, our study highlighted the sex-related difference in the association between child neglect and misperception of body weight, which was also consistent with the findings of two studies in adults ( 14 , 15 ). These studies consistently explained that females with a higher level of child maltreatment were more vulnerable to life stress ( 14 , 15 ), and it might be fueled by maladaptive strategies that used body shape to determine self-worth ( 14 ). However, it was unclear whether the explanation could be applied to children.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, our study highlighted the sex-related difference in the association between child neglect and misperception of body weight, which was also consistent with the findings of two studies in adults ( 14 , 15 ). These studies consistently explained that females with a higher level of child maltreatment were more vulnerable to life stress ( 14 , 15 ), and it might be fueled by maladaptive strategies that used body shape to determine self-worth ( 14 ). However, it was unclear whether the explanation could be applied to children.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, no study examines the association between child neglect and inaccurate BWP in children, while two studies in adults consistently indicated that child maltreatment was associated with inaccurate BWP in adulthood ( 14 , 15 ). These studies suggested that adults with higher child maltreatment may be more sensitive and vulnerable to subsequent stressors and consequently, easily misperceive their body weight ( 14 , 15 ). In addition, as for children, the maltreatment experience directly leads to maladjustment, including depression and low self-esteem ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive associations between childhood maltreatment and CVD subtypes and BMI have been reported extensively 5,36 but associations with other CVD risk factors such as blood pressure and lipids are less established. 36 We replicated previously observed associations between maltreatment increasing BMI [32][33][34] , smoking behaviour 6,37 , and decreasing SBP. 38,39 Interpretability of interactions and effect modifications Interaction and effect modification are terms commonly used interchangeably despite representing subtly different concepts.…”
Section: Results In Contextsupporting
confidence: 85%
“…Reports of sex differences in the association between childhood maltreatment subtypes and CVD have been mixed, 6,13,[32][33][34][35] however we did not identify any sex-specific differences. Replication and validation using other cohorts may elucidate whether we missed modification and sex-specific effects due to lack of statistical power.…”
Section: Results In Contextcontrasting
confidence: 82%